Fusobacterium nucleatum and colorectal cancer: A mechanistic overview. Issue 3 (7th September 2018) - Hashemi Goradel, Nasser; Heidarzadeh, Siamak; Jahangiri, Samira; Farhood, Bagher; Mortezaee, Keywan; Khanlarkhani, Neda; Negahdari, Babak
Abstract: Colorectal cancer (CRC) is the third most prevalent cancer in the world. There are many risk factors involved in CRC. According to recent findings, the tumor microenvironment and feces samples of patients with CRC are enriched by Fusobacterium nucleatum . Thus, F. nucleatum is proposed as one of the risk factors in the initiation and progression of CRC. The most important mechanisms of Fusobacterium nucleatum involved in CRC carcinogenesis are immune modulation (such as increasing myeloid‐derived suppressor cells and inhibitory receptors of natural killer cells), virulence factors (such as FadA and Fap2), microRNAs (such as miR‐21), and bacteria metabolism. The aim of this review was to evaluate the mechanisms underlying the action of F. nucleatum in CRC. Abstract : One of the probabilities in colorectal cancer (CRC) development is Fusobacterium . F. nucleatum could contribute in CRC development through virulence factors, microRNAs (miRNA), immune evasion, and increasing metastasis.